Illness Fatality Prevention at PT XYZ Zone X Through SEAGU 2.0 Wellness Program - Febrina, Indi Rahma; Lailiyah, Syifa'ul; Sugiono, Nana (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Globally, over 250 million workplace accidents and 160 million work-related illnesses occur annually, with 1.2 million resulting in deaths. In Indonesia, CVD is the leading cause of illness-related fatalities, driven by factors like hypertension, obesity, and dyslipidemia. PT XYZs parent company reported 19 such deaths in 2021, mostly from CVD. In response, Zone Xs Health Team launched the SEAGU Wellness Program to promote healthy lifestyles. This study aims to conduct research using secondary data obtained from the SEAGU 2.0 Wellness Program. This study used a descriptive quantitative method with secondary data from 153 workers annual Medical Check-Up records. Post-program results showed a reduction in dyslipidemia cases from 45 to 23 and obesity cases from 52 to 27a drop of over 50%. To improve sustainability, activities like group exercise and Health Talks should be held more frequently with stronger participant engagement.